Special feature of forming solid planar diffusion a source for submicron structure - Berezhansky, Volodymyr (Видавництво Львівської політехніки, 2010)
Solid planar diffusion a source for forming submicron structure VLSI are given in this paper.
Keywords: silane; borazine; ionic-plasma processing technique